Nature of Gender-Based Activities Toward Cross-Border Conflict Management Between Kisumu and Nandi Counties, Kenya - Okech, Robert Amiller; Onkware, Kennedy (Archives of Business Research, 2022)
Conflict management has a gendered dimension whereby both men and women play an important role through various activities in cross-border conflict management programs. However, the potential of women's activities in influencing cross-border conflict management remains unrecognized. The study sought to discuss the contribution of gender-based activities toward conflict management along the border of Kisumu and Nandi Counties. The Feminist Conflict Resolution Theory guided the study. The study was conducted in Kisumu and Nandi counties; a Descriptive survey research design was utilized during the study. The target population included household heads, government officials and civil society organizations including community-based and faith-based organizations. Both primary and secondary data were used during the study. Primary data was collected through questionnaires, Interviews and Focus Group Discussions. The study had a sample size of 453 respondents selected through simple random, Convenience and purposive sampling. Qualitative data were analyzed by use of thematic analysis and the results presented in a narrative form and through verbatim quotations, while quantitative was analyzed by using Statistical Packages for Social Scientists (SPSS) to obtain both descriptive and the findings were then be presented in form of charts, graphs and Tables. The study found that there were several gender-based activities in the area that were key to social cohesion and conflict management along the borders of the two counties. These activities included micro-finance institutions at the community level, saving and lending groups, cash transfers, youth programmes, religious peace organizations, and intermarriages among other activities. The study concluded that there are a number of gender-based activities in the study area some of which escalated the conflicts while other were helpful in managing the conflicts.